Development of Project-Based Learning Student Activity Sheets to Improve Scientific Literacy Skills on Green Chemistry Materials - Rozanah Maimun; Mitarlis Mitarlis (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The demands of 21st-century science education emphasize the development of scientific literacy and sustainability awareness, necessitating the integration of Project-Based Learning and green chemistry–oriented learning materials. This research aims to develop Student Activity Sheets (SAS) based on Project-Based Learning (PBL) to enhance students’ scientific literacy skills related to green chemistry materials. The research method used is Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate) limited to the develop stage. The research subjects were 32 grade XI students at MA Unggul Sabira-IIBS Mojokerto. The validity of SAS was assessed by two chemistry lecturers and one chemistry teacher, yielding a validity mode score of 5, indicating very valid criteria. The practicality of SAS was measured through student response questionnaires, obtaining 96.52% (very practical), learning implementation observation with mode 5 (very good), and student activity observation with mode 5 (very good). The effectiveness of SAS was measured through a pretest-posttest of scientific literacy skills with an average N-gain of 0.83 (high category). The results showed that 90% of students experienced significant improvement, with an N-gain of 0.7 or greater. The SAS developed contains three projects: eco-enzyme as organic fertilizer, cloth pads, and natural room fresheners from lime and coffee, all integrated with green chemistry principles and scientific literacy domains. Thus, the SAS based on PjBL is feasible (valid, practical, and effective) for improving students' scientific literacy skills in green chemistry materials.